2022
DOI: 10.21037/atm-21-6240
|View full text |Cite
|
Sign up to set email alerts
|

Down regulated oncogene KIF2C inhibits growth, invasion, and metastasis of hepatocellular carcinoma through the Ras/MAPK signaling pathway and epithelial-to-mesenchymal transition

Abstract: Background: Hepatocellular carcinoma (HCC) is the leading cause of cancer death. Kinesin family member 2C (KIF2C) has been shown as oncogene in a variety of tumors. However, it's role in HCC remains unclear.Methods: In this study, the expression level of KIF2C in HCC was detected by immunohistochemical staining and RT-PCR, and verified by Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA) and Oncomine database. A curve was established to evaluate the diagnostic efficiency of KIF2C. The effect of KIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…Previous research has revealed that KIF2C is substantially expressed in liver cancer (17,19,26,27), breast cancer (28), endometrial carcinoma (20), lung cancer (29,30), glioma (31), bladder cancer (32), colorectal cancer (33), esophageal squamous cell carcinoma (34), cervical cancer (18), and thyroid cancer (35). The results of our pan-cancer analysis indicated that KIF2C was highly expressed in 28 tumors, including PCa, which was consistent with previous results reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous research has revealed that KIF2C is substantially expressed in liver cancer (17,19,26,27), breast cancer (28), endometrial carcinoma (20), lung cancer (29,30), glioma (31), bladder cancer (32), colorectal cancer (33), esophageal squamous cell carcinoma (34), cervical cancer (18), and thyroid cancer (35). The results of our pan-cancer analysis indicated that KIF2C was highly expressed in 28 tumors, including PCa, which was consistent with previous results reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…According to Yang et al (18), KIF2C expression was linked to the kind of cervical cancer. In hepatocellular carcinoma, Mo et al found that KIF2C was substantially linked with pathological stage and neoplasm histological grade (17). According to Gan et al, elevated KIF2C expression in NSCLC tissues was associated with a higher T stage, poor differentiation status, and lymph node metastases (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KIF2C is upregulated in endometrial cancer (EC), which can cause a malignant phenotype in EC and negatively correlates with CD8T cells, which have cancer suppressive effects ( An et al, 2021 ). In hepatocellular carcinoma (HCC), KIF2C can promote epithelial-mesenchymal transition (EMT) for HCC progression ( Mo et al, 2022 ). Through the TGF-1/Smad signaling pathway, KIF2C promotes thyroid cancer proliferation and migration ( Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%